2018
DOI: 10.1177/1357633x18793282
|View full text |Cite
|
Sign up to set email alerts
|

It’s important, but not important enough: eHealth as a curriculum priority in medical education in Australia

Abstract: Information and communications technology has become central to the way in which health services are provided. Technology-enabled services in healthcare are often described as eHealth, or more recently, digital health. Practitioners may require new knowledge, skills and competencies to make best use of eHealth, and while universities may be a logical place to provide such education and training, a study in 2012 found that the workforce was not being adequately educated to achieve competence to work with eHeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 8 publications
2
78
0
5
Order By: Relevance
“…Therefore, education about eHealth for those involved, in this case the undergraduate students, can lessen the barriers previously mentioned and help to create a workforce that is open and able to use eHealth in their daily practice. Many universities do not have dedicated eHealth training in the current curriculum, adding to the resistance to change [ 17 , 18 ]. Universities and their executives are aware that eHealth training is important, but due to the already overcrowded curricula with competing interests, implementation is lacking [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, education about eHealth for those involved, in this case the undergraduate students, can lessen the barriers previously mentioned and help to create a workforce that is open and able to use eHealth in their daily practice. Many universities do not have dedicated eHealth training in the current curriculum, adding to the resistance to change [ 17 , 18 ]. Universities and their executives are aware that eHealth training is important, but due to the already overcrowded curricula with competing interests, implementation is lacking [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent assessment of medical curricula in Sweden showed that only one university had concrete plans about implementing eHealth into their medical curriculum [ 17 ]. Another trial in Australia showed that none of the universities had established an eHealth program [ 18 ]. In addition, the European Health Parliament found that current health professionals do not feel adequately trained in eHealth and found that formal eHealth training is lacking from an early stage in the training of medical professionals [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, the institution of telehealth services have been recommended by the World Health Organization across primary health and specialist services in an effort to minimize the discrepancy in healthcare opportunities faced by rural patients . Continuous advancements in technology and improved internet connectivity have allowed for the digitization of services to push past the archaic boundaries of strictly in‐person, health facility delivered care models …”
mentioning
confidence: 99%
“…Those who are not willing to engage often list a major barrier to the uptake of telehealth as the increased time per consultation when compared with in‐person appointments . Improvement in telehealth skills for delivery is paramount, yet despite this, Australian medical education systems have failed to adopt telehealth education into their curriculums citing competing topics of equal importance . The DIT involved in these consultations was 3 years post‐graduation and had received no formal education, either in university or prior to commencing teleconsultations.…”
mentioning
confidence: 99%